Falsafah Fagogoru:Konstruksi Teologi Perdamaian- Kontekstual di Halmahera Tengah - Hendry R Sipahelut (Program Pascasarjana UKIM, 2021)
This paper will examine the Fagogoru philosophy as a contextual theological study of peace in Lelilef Sawai village and Lelilef Woebulen village, Weda Tengah District, Central Halmahera Regency. Central Halmahera Regency is located on the island of Halmahera which is the largest island in North Maluku. In order to be able to deepen the study further, there are three key questions in this study, namely: (1) How did Fagogoru's philosophy shape the life practices of the people of Lelilef Sawai village and Lelilef Woebulen village based on the Fagogoru philosophy? (2) What are the life values contained in Fagogoru's philosophy? (3) How to reconstruct contextual theology from Fagogoru's philosophy as an effort to build inter-religious harmony in Weda District, Central Halmahera?. It is hoped that this research can contribute ideas for developing peace studies, as well as developing studies on the relationship between religion and culture. In addition, it can also be a model for the community and the church in an effort to build and maintain harmony in the midst of the plurality of the people of Halmahera, North Maluku by making local culture the basis for peace.